Factors Associated with Parental Refusal for Lumber Puncture Among Children and Adolescent: A Cross Sectional Survey at a Tertiary Care Hospital - Sana Samreen, Mahnaz Hakeem, Hafsa Zaheer, Ambreen Raza, Abdul Gaffar Billoo, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The lumbar puncture is frequently used in medical facilities to collect data on the cerebrospinal fluid (CSF). The method aids in the diagnosis of conditions affecting the spine and brain's central nervous system. However, in routine practice out of the many challenges posed by the parents due to lack of education, denial of consent for this procedure is a great challenge at clinical settings. Objectives: To determine the association of various factors with parental refusal for lumbar puncture among pediatric population (age from 1 moth to 18 years). Materials and Methods: A descriptive, cross-sectional study was carried out at the department of pediatrics and child health and department of Emergency at Aga Khan University Hospital, Karachi from June 2017 to May 2018. A total of 178 children 1 month to 18 years old admitted with febrile fits, suspected meningitis or encephalitis who were advised for lumber puncture were included. Results: In the present study, the age of the patients ranged from 1 month to 18 year. Majority of the patients 153 (85.39%) were between 1 month to 6 years of age. There were 115 (64.61%) male patients.. Fever and fits was the most frequent indication (n=151, 84.83%) for lumber puncture in the study. Most of the parents were educated, 68.54% of mothers and 65.17% fathers had graduate level of education, and parents of 47 (26.4%) patients refused for lumber puncture. Conclusion: This study concluded that frequency of parental refusal for lumbar puncture was 26.4% and the most common reason for refusal was fear of complications. Keywords: lumbar puncture, febrile seizures, parental refusal.